Do mouthwashes affect the optical properties of resin cement? - Nazire Nurdan Çakır Kılınç; Pınar Yıldız (BMC, 2024)
Abstract Objectives The objective of this study was to evaluate the effect of mouthwashes on the optical properties of resin cement. Materials and methods One hundred and 60 resin cement discs (6x2mm) were produced from 4 different brands of resin cement (Panavia V5, Estecem II, RelyX Veneer, NX3) with the help of a Teflon mould. The discs were divided into 4 subgroups, 1 of which served as the control group, to be immersed in mouthwashes after measuring the initial L, a, and b values on white and black backgrounds. Colour measurements were repeated after the 1st and 7th days. The collected data were used to calculate the ∆E00 value to measure colour stability, the translucency parameter (TP00), and the contrast ratio parameter (CR) to compare translucency change. Data were statistically analysed using mixed-design analysis of ANOVA and the Bonferroni-Dunn test. Repeated measures ANOVA was used for dependent results (α = 0.05). Results On the ∆E00, TP00, and CR parameters; the joint effect of resin groups, mouthwash groups, and measurement times were found to be statistically significant. The ∆E00 (colour difference) parameter; the joint effect of resin groups, mouthwash groups, and measurement times was found to be statistically significant. The TP00; the joint effect of resin groups, mouthwash groups, and measurement times were found to be statistically significant. The CR parameter; the joint effect of resin groups, mouthwash groups, and measurement times was found to be statistically significant. In the Estecem II (Tokuyama) group, the means of Listerine Cool Mint (Johnson & Johnson) was above acceptable limits in both time periods. In the Panavia V5 (Kuraray Noritake) group, the color change was above acceptable limits in all time periods and in all mouthwash groups. Among the resin materials used, Estecem II (Tokuyama) shows the most color change. Listerine Cool Mint (Johnson & Johnson) caused more color change than other mouthwashes at all times. Conclusions Within the limitations of this study; the colour stability and translucency value of resin cement depend on both the resin cement content and the mouthwash. Long-term use of mouthwash may adversely affect the optical properties of the resin cement. Clinical relevance Clinicians should take into account the fact that mouthwash use and the composition of the resin cement employed will have an impact on the colour of laminate veneers.